‘Without Partners our Hands are tied!’ Exploring Multi-stakeholder Partnerships on Migration and Displacement in African Intermediary Cities - Stürner-Siovitz, Janina; Morthorst, Lasse Juhl (Urban Migrant Inclusion and Refugee Protection - Volume 2, 2025)
Scholars and policymakers addressing African urbanisation have, to date, predominantly focused on migration and refugee movements into major urban areas and capital cities. In contrast, intermediary cities, the in-between the rural and the metropolitan, have been largely absent from academic debates. Addressing this gap is essential, as African intermediary cities are increasingly impacted by mixed migration movements and (inter)national policies but often remain without adequate legal mandates as well as financial and human resources to accommodate and protect vulnerable migrants and refugees. Therefore, some local authorities have begun to engage in multi-stakeholder partnerships, bringing together local, national, and international actors. Based on research collaborations of the Equal Partnerships project with six intermediary cities—Garissa in Kenya, Gulu in Uganda, Kumasi in Ghana, Oujda in Morocco, Saint Louis in Senegal, and Sfax in Tunisia—this chapter explores risks and opportunities of such partnerships and presents a set of policy recommendations.
CRIS-Team Scopus Importer:2025-09-05
Keywords: Displacement; Governance; Intermediary cities; Migration; Multi-stakeholder partnerships